Epigenetic regulation mechanism of folic acid deficiency inhibiting Brachyury expression and its effect on differentiation of embryoid bodies - CHANG Shaoyan; GUO Jiuye; CHEN Yan (陆军军医大学学报, 2022)
Objective To investigate the epigenetic regulation mechanism of folic acid deficiency in inhibition of the expression of Brachyury, a key developmental gene, and its effect on the differentiation of embryoid bodies (EBs). Methods Firstly, the cell model of folic acid-deficient embryonic stem cells (ESCs) differentiated into EBs was established. According to the folate level, they were divided into normal group, folate deficiency group and folate supplement group. MassARRAY system and RT-PCR were used to detect the methylation and expression level of Brachyury gene in EBs to clarify the effect of the deficiency on the expression. RT-PCR and chromatin immunoprecipitation (ChIP)-qPCR were used to detect the expression of DNA methylase and histone methylation modification, respectively to explore the epigenetic regulation mechanism of folic acid deficiency on Brachyury expression. At the same time, the expression levels of pluripotent markers and triploblastic markers were detected to explore the effect of abnormal expression of Brachyury on EBs differentiation. Results ① In the differentiation of ESCs into EBs under folic acid deficiency, the expression level of Brachyury was decreased significantly, only 0.19±0.08 times of that in the normal group, and folate supplementation increased the level to 0.62±0.14 times of that of the normal group. The methylation level of promoter region of Brachyury in EBs was increased from (30.75±0.5)% in the normal group to (37.93±1.24)% in the folic acid-deficient group, and decreased to (31.88±2.67)% after folic acid supplementation. ② The expression level of DNMT3b, DNA de novo methylase, in folic acid-deficiency group was increased by 1.59±0.31 times higher than that of normal group. H3K27me3 modification was enhanced in the EBs with folate deficiency, and the relative enrichment level was 0.22±0.03 in the normal group, 0.32±0.02 in the folate deficiency group, and 0.24±0.01 in the folate supplement group. ③After the differentiation of folic acid-deficient ESCs into EBs, the cell morphology was significantly changed with the smaller EBs spheres and irregular shape. Folic acid supplementation resulted in normal volume and regular shape of EBs spheres. ④ ESCs pluripotent markers, Nanog and Sox2, were significantly up-regulated, and their relative levels in EBs of folate deficiency group was 3.18±0.95 and 4.23±1.59 times higher than those of normal group. The expression of ectodermal marker Fgf5 and mesodermal marker Gsc in folic acid-deficient EBs were significantly down-regulated, which was 0.42±0.04 times and 0.61±0.20 times in folic acid-deficient EBs when compared with those in normal EBs, respectively. Conclusion Through the dual epigenetic regulation of DNA methylation and histone H3K27 methylation, folic acid deficiency causes significant down-regulation of Brachyury and ultimately leads to the blocked differentiation of EBs.